Gas barrier layered body, and packaging material and tube container using the same

The gas barrier laminate, featuring a polyolefin substrate and polyvinyl alcohol-based resin layers with a Si or Al-containing thin film layer, addresses the challenge of achieving both excellent gas barrier properties and recyclability in polyolefin-based packaging materials, ensuring performance and environmental sustainability.

JP2025071278APending Publication Date: 2025-05-02TOPPAN HOLDINGS INC
View PDF 18 Cites 0 Cited by

Patent Information

Application Number
JP2025027098
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2019-07-29
Filing Date
2025-02-21
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

Polyolefin-based packaging materials struggle to achieve both excellent gas barrier properties and recyclability, especially when subjected to hot water treatment.

Method used

A gas barrier laminate comprising a polyolefin substrate layer, a first polyvinyl alcohol-based resin layer, a Si or Al-containing thin film layer, and a second polyvinyl alcohol-based resin layer, which provides enhanced gas barrier properties and maintains these properties even after sterilization.

Benefits of technology

The laminate achieves excellent gas barrier properties and recyclability, allowing for the production of monomaterial packaging that meets environmental recycling demands while maintaining performance under hot water treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025071278000001_ABST
    Figure 2025071278000001_ABST
Patent Text Reader

Abstract

To provide a polyolefin-based gas barrier layered body that is useful for attaining excellent recyclability of a packaging material and has excellent gas barrier properties.SOLUTION: The present disclosure relates to a gas barrier layered body including: a substrate layer containing a polyolefin-based resin; a first polyvinyl alcohol-based resin layer; a Si or Al-containing thin film layer; and a second polyvinyl alcohol-based resin layer, in the stated order, wherein the first polyvinyl alcohol-based resin layer has a logarithmic decrement at 100°C of 0.20 or less and a logarithmic decrement at 125°C of 0.30 or less, as measured by means of a rigid-body pendulum type physical property testing instrument, and wherein the second polyvinyl alcohol-based resin layer has an indentation hardness of 0.5 to 1.0 GPa as determined by means of a nanoindenter.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a gas barrier laminate, and a packaging material and a tube container using the same. [Background technology]

[0002] Gas barrier laminates, which are a combination of a plastic film substrate and a layer of an inorganic compound such as silicon oxide, aluminum oxide, or magnesium oxide, are widely used for packaging items that require blocking various gases such as water vapor and oxygen. Various improvements have been considered for such gas barrier laminates with the aim of preventing a decrease in gas barrier properties and further improving the barrier properties. For example, Patent Document 1 discloses a gas barrier laminate characterized by having, in this order, a substrate having a polyethylene naphthalate layer, a layer made of a composition containing an acrylic polyol and an isocyanate compound, and an inorganic thin film layer. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2013-49266 A Summary of the Invention [Problem to be solved by the invention]

[0004] In recent years, due to the heightened environmental awareness triggered by the problem of marine plastic waste, etc., there is a demand for further improved efficiency in the sorting and recovery of plastic materials and their recycling. That is, even in soft packaging materials, which have traditionally been made high-performance by combining various different materials, there is a demand for mono-materialization. However, when attempting to realize mono-materialization using polyolefin resins, the reality is that it is difficult to obtain good barrier properties and hot water treatment resistance.

[0005] The present disclosure aims to provide a polyolefin-based gas barrier laminate that is useful for realizing excellent recyclability of packaging materials and has excellent gas barrier properties, and to provide a packaging material and a tube container using the gas barrier laminate. [Means for solving the problem]

[0006] One aspect of the present disclosure provides a gas barrier laminate comprising a base layer, a first polyvinyl alcohol-based resin layer, a Si- or Al-containing thin film layer, and a second polyvinyl alcohol-based resin layer in this order. In the gas barrier laminate, the base layer contains a polyolefin-based resin, and the first polyvinyl alcohol-based resin layer has a logarithmic decrement at 100°C of 0.20 or less and a logarithmic decrement at 125°C of 0.30 or less on the surface of the first polyvinyl alcohol-based resin layer that contacts the Si- or Al-containing thin film layer, as measured by a rigid pendulum-type physical property tester, and the surface of the second polyvinyl alcohol-based resin layer has an indentation hardness of 0.5 to 1.0 GPa using a nanoindenter. Polyolefin-based resins generally have lower barrier properties as a base material than polyester-based resins such as PET, and are soft, so that they are prone to degradation during processing and sterilization. In contrast, the gas barrier laminate has a Si- or Al-containing thin film layer sandwiched (sandwiched) between first and second polyvinyl alcohol-based resin layers on a polyolefin substrate, and thus has excellent gas barrier properties. Furthermore, since the polyvinyl alcohol-based resin layer itself has predetermined physical properties, even if a sterilization treatment is performed at a high temperature of, for example, 100°C or higher, the thin film layer held on the soft polyolefin substrate is protected, and the barrier properties can be maintained even after the sterilization treatment.

[0007] One aspect of the present disclosure provides a packaging material including the gas barrier laminate and a sealant layer provided on a surface of the gas barrier laminate opposite to the base layer.

[0008] One aspect of the present disclosure provides a tube container comprising a tubular body portion having one end closed and a spout portion attached to the other end of the body portion, the body portion being composed of a film including the gas barrier laminate and a layer of unstretched polyolefin.

[0009] The gas barrier laminate achieves excellent gas barrier properties by a sandwich structure using polyvinyl alcohol-based resin layers, and therefore the resin material for the substrate layer can be made more flexible. This has the advantage that the resin material for the substrate layer can be easily matched with the resin material for the sealant layer. For example, a mono-material packaging material can be realized by using a substrate layer made of a polyolefin-based resin in combination with a sealant layer made of a polyolefin-based resin. In the present disclosure, a mono-material packaging material refers to a packaging material in which the mass ratio of a specific material (e.g., polyolefin-based resin) is 90% by mass or more. Effect of the Invention

[0010] According to the present disclosure, there is provided a polyolefin-based gas barrier laminate that is useful for realizing excellent recyclability of packaging materials and has excellent gas barrier properties. According to the present disclosure, there are provided a packaging material and a tube container using the gas barrier laminate. [Brief description of the drawings]

[0011] [Figure 1] FIG. 1 is a schematic cross-sectional view showing a laminate according to one embodiment. [Diagram 2] FIG. 2 is a schematic cross-sectional view showing a packaging material according to one embodiment. [Diagram 3] FIG. 3 is a schematic cross-sectional view showing a packaging material according to one embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] Hereinafter, preferred embodiments of the present disclosure will be described in detail with reference to the drawings as needed. In the drawings, the same or corresponding parts are denoted by the same reference numerals, and duplicated explanations will be omitted. In addition, the dimensional ratios of the drawings are not limited to the ratios shown in the drawings.

[0013] <Gas barrier laminate> Fig. 1 is a schematic cross-sectional view showing a gas barrier laminate according to one embodiment. The gas barrier laminate 100 shown in Fig. 1 includes a base layer 10, a first polyvinyl alcohol-based resin layer 11, a Si- or Al-containing thin film layer 12, and a second polyvinyl alcohol-based resin layer 13, in this order.

[0014] (base material layer) The substrate layer is a film that serves as one of the supports and contains a polyolefin resin.

[0015] Examples of polyolefin resins include polyethylene (PE), polypropylene (PP), polybutene (PB), and cycloolefin polymers. Examples of polyolefin resins include acid-modified polyolefins obtained by graft-modifying polyolefins with unsaturated carboxylic acids, acid anhydrides of unsaturated carboxylic acids, esters of unsaturated carboxylic acids, and the like. Small amounts of second and third components such as ethylene and butene may be used as raw material monomers in the synthesis of polypropylene. From the viewpoint of excellent heat resistance, a monopolymer film of propylene can be used as the base layer.

[0016] The film constituting the base layer may be a stretched film or a non-stretched film. However, from the viewpoint of impact resistance, heat resistance, water resistance, dimensional stability, etc., the film constituting the base layer may be a stretched film. The stretching method is not particularly limited, and any method may be used as long as a dimensionally stable film can be provided, such as stretching by inflation, uniaxial stretching, or biaxial stretching.

[0017] The thickness of the substrate layer is not particularly limited, but from the viewpoint of obtaining excellent impact resistance and excellent gas barrier properties, it can be from 9 to 100 μm, and may be from 15 to 30 μm.

[0018] The film constituting the base layer may be subjected to various pretreatments such as corona treatment, plasma treatment, and frame treatment on the lamination surface within the scope of not impairing the barrier performance, or a coating layer such as an easy-adhesion layer may be provided.

[0019] The film constituting the base layer may contain additives such as antistatic agents, ultraviolet absorbers, plasticizers, and slipping agents, if necessary.

[0020] (First polyvinyl alcohol-based resin layer) The polyvinyl alcohol resin may be any resin having a vinyl alcohol unit formed by saponifying a vinyl ester unit, such as polyvinyl alcohol (PVA) or ethylene-vinyl alcohol copolymer (EVOH). From the viewpoint of heat resistance and gas barrier properties, EVOH is preferably used.

[0021] Examples of PVA include resins obtained by polymerizing vinyl esters such as vinyl acetate, vinyl formate, vinyl propionate, vinyl valerate, vinyl caprate, vinyl laurate, vinyl stearate, vinyl pivalate, and vinyl versatate alone, followed by saponification.

[0022] The PVA may be a copolymerized or post-modified modified PVA. The copolymerized modified PVA can be obtained, for example, by copolymerizing a vinyl ester with an unsaturated monomer copolymerizable with the vinyl ester, followed by saponification. The post-modified PVA can be obtained by copolymerizing an unsaturated monomer in the presence of a polymerization catalyst with the PVA obtained by polymerizing a vinyl ester and then saponifying it. The amount of modification in the modified PVA can be less than 50 mol% from the viewpoint of exhibiting sufficient gas barrier properties, and can be 10 mol% or more from the viewpoint of obtaining the effect of modification.

[0023] Examples of the unsaturated monomer include olefins such as ethylene, propylene, isobutylene, α-octene, α-dodecene, and α-octadecene; hydroxyl group-containing α-olefins such as 3-buten-1-ol, 4-pentyn-1-ol, and 5-hexen-1-ol; unsaturated acids such as acrylic acid, methacrylic acid, crotonic acid, maleic acid, maleic anhydride, itaconic acid, and undecylenic acid; nitriles such as acrylonitrile and methacrylonitrile; amides such as diacetone acrylamide, acrylamide, and methacrylamide; and ethylene. Examples of suitable unsaturated monomers include olefin sulfonic acids such as ethylene sulfonic acid, allyl sulfonic acid, and methallyl sulfonic acid; vinyl compounds such as alkyl vinyl ether, dimethyl allyl vinyl ketone, N-vinyl pyrrolidone, vinyl chloride, vinyl ethylene carbonate, 2,2-dialkyl-4-vinyl-1,3-dioxane, glycerin monoallyl ether, and 3,4-diacetoxy-1-butene; vinylidene chloride, 1,4-diacetoxy-2-butene, vinylene carbonate, polyoxypropylene, and polyoxypropylene vinylamine. From the viewpoint of gas barrier properties, the unsaturated monomer may be an olefin, and may in particular be ethylene.

[0024] Examples of the polymerization catalyst include radical polymerization catalysts such as azobisisobutyronitrile, benzoyl peroxide, lauryl peroxide, etc. The polymerization method is not particularly limited, and bulk polymerization, emulsion polymerization, solvent polymerization, etc. can be adopted.

[0025] The polymerization degree of PVA is preferably 300 to 3000. If the polymerization degree is less than 300, the barrier property is likely to decrease, and if it exceeds 3000, the viscosity is too high and the coating suitability is likely to decrease. The saponification degree of PVA is preferably 80 mol% or more, more preferably 90 mol% or more, and even more preferably 98 mol% or more. The saponification degree of PVA may be 100 mol% or less, or 99.9 mol% or less. The polymerization degree and saponification degree of PVA can be measured according to the method described in JIS K 6726 (1994).

[0026] EVOH is generally obtained by saponifying a copolymer of ethylene and an acid vinyl ester such as vinyl acetate, vinyl formate, vinyl propionate, vinyl valerate, vinyl caprate, vinyl laurate, vinyl stearate, vinyl pivalate, or vinyl versatate.

[0027] The ethylene unit content of EVOH is 10 mol% or more, more preferably 15 mol% or more, even more preferably 20 mol% or more, and particularly preferably more than 35 mol%. The ethylene unit content of EVOH is preferably 65 mol% or less, more preferably 55 mol% or less, and even more preferably less than 50 mol%. When the ethylene unit content is 10 mol% or more, the gas barrier property or dimensional stability can be maintained well under high humidity. On the other hand, when the ethylene unit content is 65 mol% or less, the gas barrier property can be improved. The ethylene unit content of EVOH can be determined by NMR method.

[0028] The saponification can be carried out with an alkali or an acid, but from the viewpoint of the saponification rate, an alkali can be used. Examples of the alkali include alkali metal hydroxides such as sodium hydroxide and potassium hydroxide, and alkali metal alkoxides such as sodium ethylate, potassium ethylate, and lithium methylate.

[0029] The thickness of the first polyvinyl alcohol-based resin layer is not particularly limited, but from the viewpoints of barrier properties and processability, it can be 0.05 to 5 μm, may be 0.1 to 2 μm, or may be 0.3 to 1 μm.

[0030] The mass per unit area of ​​the first polyvinyl alcohol-based resin layer is 0.1 to 10 g / m 2 This mass can be set to 0.1 g / m 2 If the mass is 10 g / m or more, the surface 11a of the first polyvinyl alcohol-based resin layer can be formed sufficiently smooth even if the surface 10a of the base layer is insufficiently smooth, and a Si- or Al-containing thin film layer having excellent gas barrier properties can be formed on the surface 11a. 2The above-mentioned is advantageous in terms of realizing a mono-material packaging material and reducing material costs.

[0031] The surface roughness Sa of the surface 11a of the first polyvinyl alcohol-based resin layer can be, for example, 0.2 μm or less, and may be 0.01 to 0.1 μm or 0.02 to 0.1 μm. When the surface roughness Sa of the surface 11a is 0.2 μm or less, a Si- or Al-containing thin film layer having excellent gas barrier properties can be formed on the surface 11a. On the other hand, when the surface roughness Sa of the surface 11a is 0.01 μm or more, the adhesion between the first polyvinyl alcohol-based resin layer and the Si- or Al-containing thin film layer can be improved by the anchor effect compared to when the surface roughness Sa is less than 0.01 μm. The value of the surface roughness Sa here means a value measured using VertScan (manufactured by Ryoka Systems Co., Ltd.).

[0032] According to the study by the present inventors, for example, when a propylene monopolymer film (monopolymer layer) is used as a substrate layer, the propylene monopolymer film has excellent heat resistance, but has the disadvantage that its surface is easily vein-like. Therefore, even if a Si- or Al-containing thin film layer is directly formed on the surface, sufficient barrier properties cannot be achieved. Therefore, by interposing a polyvinyl alcohol-based resin layer between the propylene monopolymer film and the Si- or Al-containing thin film layer, excellent gas barrier properties can be achieved. By using a propylene monopolymer film as a substrate layer and a polypropylene-based resin film as a sealant layer in combination, a monomaterial packaging material can be produced.

[0033] From the viewpoint of achieving excellent oxygen barrier properties on the surface 11a of the first polyvinyl alcohol-based resin layer, the logarithmic attenuation rate at 100°C measured by a rigid pendulum-type physical property tester is 0.20 or less, may be 0.18 or less, or may be 0.15 or less. The lower limit of the logarithmic attenuation rate is not particularly limited, but may be 0.01 or more from the viewpoint of suppressing film cracking during sterilization treatment due to the film becoming too hard, and may be 0.1 or more from the viewpoint of easily maintaining excellent oxygen barrier properties. Also, from the viewpoint of achieving excellent oxygen barrier properties on the surface 11a of the first polyvinyl alcohol-based resin layer, the logarithmic attenuation rate at 125°C measured by a rigid pendulum-type physical property tester is 0.30 or less, may be 0.28 or less, or may be 0.25 or less. The lower limit of the logarithmic attenuation rate is not particularly limited, but may be 0.01 or more from the viewpoint of suppressing film cracking during sterilization treatment due to the film becoming too hard, and may be 0.1 or more from the viewpoint of easily maintaining excellent oxygen barrier properties. This logarithmic attenuation can be measured by the rigid pendulum method, for example, using an A&D rigid pendulum type physical property tester RPT-3000W. Using an RBP-020 as the pipe edge, the measurement is performed by heating from 30°C to 130°C at a heating rate of 10°C / min. Measurements are performed at three locations under these conditions, and the average logarithmic attenuation at 100°C and 125°C is calculated. A small logarithmic attenuation means that the resin molecules that make up the surface of the object being measured are less likely to move even when exposed to heat.

[0034] (Si or Al-containing thin film layer) Examples of the Si or Al (atom)-containing compound contained in the Si or Al-containing thin film layer include metal oxides such as silicon oxide (SiOx) and aluminum oxide (AlOx), metal aluminum (Al), silicon nitride (SiN), and silicon oxynitride (SiON). From the viewpoint of transparency and barrier properties, the Si or Al-containing compound may be aluminum oxide and silicon oxide. Also, from the viewpoint of excellent tensile elongation during processing, the Si or Al-containing compound may be silicon oxide. By using the Si or Al-containing thin film layer, it is possible to obtain high barrier properties while suppressing the thickness.

[0035] The thickness of the Si- or Al-containing thin film layer can be 5 to 80 nm. When the thickness is 5 nm or more, sufficient gas barrier properties are easily obtained. When the thickness is 80 nm or less, cracks caused by deformation due to internal stress of the thin film are suppressed, and deterioration of gas barrier properties is easily suppressed. Note that, when the thickness exceeds 80 nm, costs tend to increase due to an increase in the amount of material used and a prolonged film formation time, which is not preferable from an economical point of view. From the above viewpoint, the thickness of the Si- or Al-containing thin film layer may be 10 to 50 nm, or 20 to 40 nm.

[0036] (Second polyvinyl alcohol-based resin layer) With regard to the polyvinyl alcohol-based resin constituting the second polyvinyl alcohol-based resin layer, the contents explained in the section regarding the first polyvinyl alcohol-based resin layer can be referred to.

[0037] The second polyvinyl alcohol-based resin layer may contain Si. Specifically, the second polyvinyl alcohol-based resin layer may be a cured product of a raw material containing a polyvinyl alcohol-based resin and a silane compound. Examples of the silane compound include tetraalkoxysilanes such as tetramethoxysilane and tetraethoxysilane, and silazanes such as hexamethyldisilazane. Examples of the silane compound include compounds generally used as silane coupling agents and polysiloxane compounds having siloxane bonds. Examples of the silane coupling agent include epoxysilanes (glycidoxypropyltrimethoxysilane, etc.), (meth)acrylsilanes (acryloxypropyltrimethoxysilane, etc.), aminosilanes, ureidosilanes, isocyanate silanes, isocyanurate silanes (tris(3-trialkoxysilylpropyl)isocyanurate, etc.), and mercaptosilanes.

[0038] When forming the second polyvinyl alcohol-based resin layer, the amount of the silane compound in the above raw material can be 0.3 to 5.0 parts by mass, or alternatively 0.4 to 4.5 parts by mass, or alternatively 0.5 to 4.0 parts by mass, per part by mass of the polyvinyl alcohol-based resin, from the viewpoint of maintaining adhesion to the Si- or Al-containing thin film layer and gas barrier properties.

[0039] The thickness of the second polyvinyl alcohol-based resin layer is not particularly limited, but from the viewpoints of barrier properties and processability, it can be 0.05 to 2 μm, may be 0.1 to 0.6 μm, or may be 0.2 to 0.5 μm.

[0040] In order to achieve excellent oxygen barrier properties on surface 13a of the second polyvinyl alcohol-based resin layer, i.e., the surface not in contact with the Si- or Al-containing thin film layer, the indentation hardness by a nanoindenter is 0.5 to 1.0 GPa, optionally 0.65 to 0.95 GPa, or optionally 0.8 to 0.9 GPa.

[0041] <Method of manufacturing gas barrier laminate> The gas barrier laminate can be produced, for example, by a production method including the steps of forming a first polyvinyl alcohol-based resin layer on a base layer, forming a Si- or Al-containing thin film layer on the first polyvinyl alcohol-based resin layer, and forming a second polyvinyl alcohol-based resin layer on the Si- or Al-containing thin film layer.

[0042] (Step of forming first polyvinyl alcohol-based resin layer) In this step, a coating liquid containing a polyvinyl alcohol-based resin and a liquid medium can be used. The coating liquid can be obtained, for example, by dissolving a powder of a polyvinyl alcohol-based resin obtained by synthesis in a liquid medium. Examples of the liquid medium include water, dimethyl sulfoxide, dimethylformamide, dimethylacetamide, N-methylpyrrolidone, various glycols, polyhydric alcohols such as trimethylolpropane, and amines such as ethylenediamine and diethylenetriamine. These may be used alone or in combination of two or more. From the viewpoint of reducing environmental load, water can be used as the liquid medium. In this case, the coating liquid can be obtained by dissolving a powder of a polyvinyl alcohol-based resin in water at a high temperature (for example, 80°C).

[0043] The content of the polyvinyl alcohol-based resin (solid content) in the coating liquid can be set to 3 to 20% by mass in order to maintain good coating properties.

[0044] The coating liquid may contain additives such as isocyanate and polyethyleneimine to improve adhesion, and may also contain additives such as preservatives, plasticizers, alcohols, and surfactants.

[0045] The coating liquid can be applied to the substrate layer by any suitable method. The coating liquid can be applied by a wet film forming method using, for example, a gravure coater, a dip coater, a reverse coater, a wire bar coater, a die coater, etc. The application temperature and drying temperature of the coating liquid are not particularly limited, and can be, for example, 50° C. or higher.

[0046] The first polyvinyl alcohol-based resin layer may be formed on the substrate layer by extrusion. In the case of extrusion, multi-layer extrusion using a T-die can be adopted. An example of an adhesive that can be used during extrusion is a maleic anhydride-modified polypropylene resin.

[0047] The adhesive component may be applied onto a substrate layer and then dried to form an adhesive layer on the substrate layer in advance.

[0048] The thickness of the adhesive layer can be set to 0.1 to 50 μm, and may be 0.5 to 20 μm, from the viewpoints of adhesiveness, followability, processability, and the like.

[0049] (Step of forming a Si or Al-containing thin film layer) The Si- or Al-containing thin film layer can be formed, for example, by vacuum deposition. In the vacuum deposition, physical vapor deposition or chemical vapor deposition can be used. Examples of physical vapor deposition include, but are not limited to, vacuum deposition, sputtering, and ion plating. Examples of chemical vapor deposition include, but are not limited to, thermal CVD, plasma CVD, and photo CVD.

[0050] In the vacuum film formation, resistance heating vacuum deposition, EB (Electron Beam) heating vacuum deposition, induction heating vacuum deposition, sputtering, reactive sputtering, dual magnetron sputtering, plasma enhanced chemical vapor deposition (PECVD), etc. are particularly preferably used. However, in terms of productivity, the vacuum deposition is currently the most superior. As a heating means for the vacuum deposition, it is preferable to use any of the electron beam heating method, resistance heating method, and induction heating method.

[0051] (Step of forming second polyvinyl alcohol-based resin layer) In this step, a coating liquid can be used in the same manner as in the step of forming the first polyvinyl alcohol-based resin layer. For the coating liquid, the contents described in the section on the step of forming the first polyvinyl alcohol-based resin layer can be referred to.

[0052] The coating liquid for forming the second polyvinyl alcohol-based resin layer may contain a silane compound. The content of the silane compound in the coating liquid may be adjusted so that a desired amount of the silane compound is contained relative to the amount of the polyvinyl alcohol-based resin.

[0053] When the coating liquid contains a silane compound, the coating liquid may further contain an acid catalyst, an alkali catalyst, a photopolymerization initiator, and the like.

[0054] <Packaging material> The packaging material includes the gas barrier laminate and a sealant layer provided on the surface of the gas barrier laminate. The sealant layer may be a layer containing a polyolefin resin or a polyester resin. Figures 2 and 3 are schematic cross-sectional views showing a packaging material according to an embodiment.

[0055] The packaging material 200 shown in Fig. 2 comprises a gas barrier laminate 100 and a sealant layer 14 provided on the surface of the gas barrier laminate 100 opposite the base material layer (on the surface 13a of the second polyvinyl alcohol-based resin layer). For example, when the base material layer 10 and the sealant layer 14 are both made of polyolefin-based resin, the content of the polyolefin-based resin can be 90% by mass or more (preferably 95% by mass or more) based on the total mass of the packaging material 200. Such a packaging material 200 can be realized as a mono-material.

[0056] In the above embodiment, the packaging material 200 in which the sealant layer 14 is laminated to the surface of the barrier layer side of the gas barrier laminate 100 has been exemplified, but the sealant layer 14 may be laminated to the surface of the base layer 10 side of the gas barrier laminate 100 (see FIG. 3). The packaging material 300 shown in FIG. 3 has a configuration in which the barrier layer side of the gas barrier laminate 100 faces a general OPP film 15 (printing base material, etc.), and the sealant layer 14 is laminated to the base layer 10 side of the gas barrier laminate 100.

[0057] <Tube container> The gas barrier laminate can also be used in a tube container. Specifically, in a tube container having a tubular body with one end closed and a spout attached to the other end of the body, a film containing the gas barrier laminate and a layer of unstretched polyolefin is used in the body, so that the body is made almost entirely of polyolefin and has barrier properties. In a typical tube container, a film in which the gas barrier laminate is sandwiched between layers of unstretched polyolefin is used in the body.

[0058] The thickness of the film constituting the body portion can be, for example, 30 to 300 μm. As the material constituting the base material and the unstretched polyolefin of the gas barrier laminate, polypropylene is preferable from the viewpoint of heat resistance. In this case, if a resin material mainly composed of polypropylene, which is the same resin as that of the base material, is selected for the spout portion, it is preferable because recycling can be performed without separating the tube container body. EXAMPLES

[0059] The present disclosure will be described in more detail below with reference to experimental examples, but the present disclosure is not limited to these experimental examples.

[0060] <Preparation of Laminate> The following was prepared as the base layer. PET film: P60 (Toray Industries, Inc., thickness 12 μm) OPP film A: M-1 (manufactured by Mitsui Chemicals Tocello Co., Ltd., thickness 20 μm) OPP film B: A film made by co-extrusion of homopolypropylene resin Prime Polypro (manufactured by Prime Polymer Co., Ltd., thickness 18 μm) and adhesive resin Admer (manufactured by Mitsui Chemicals, Inc., thickness 1 μm) PE film: Stretched high-density polyethylene film (Tokyo Ink Co., Ltd., product name: SMUQ, thickness 25 μm)

[0061] The following coating solutions were prepared: PVA coating solution: JF-05 (manufactured by Nippon Vinyl Acetate & Poval Co., Ltd.) PVA coating solution (containing TEOS): JF-05 mixed with TEOS. The mixing amounts were adjusted so that the mass ratio of polyvinyl alcohol resin to TEOS was the value shown in the table. Ethylene-modified PVA coating solution: Exeval RS2817SB (Kuraray Co., Ltd.) EVOH coating solution Polyurethane coating liquid: Takenate A65 (Mitsui Chemicals, Inc.)

[0062] (Experimental Example 1) A PVA coating solution was applied onto the surface of a PET film (first layer: base layer), and then dried to form a PVA layer (second layer: first polyvinyl alcohol-based resin layer). The mass per unit area of ​​the PVA layer was 0.5 g / m 2 The thickness of the PVA layer was 0.5 μm. The surface roughness Sa of the surface of the PVA layer was 0.32 μm. The surface roughness Sa was measured using a VertScan (manufactured by Ryoka Systems Co., Ltd.).

[0063] A SiOx film (third layer) was formed on the surface of the PVA layer using an electron beam heating vacuum deposition device. That is, the SiO deposition material was evaporated by electron beam heating to form a SiOx film (thickness 30 nm).

[0064] Next, a PVA layer containing Si (fourth layer: second polyvinyl alcohol-based resin layer) was formed on the surface of the SiOx film. Specifically, TEOS, methanol, and hydrochloric acid (0.1N) were mixed in a mass ratio of 18 / 10 / 72 to obtain a hydrolyzed solution (TEOS-containing solution). A coating solution was prepared by mixing a 5% aqueous solution of PVA and a TEOS-containing solution in a mass ratio of PVA to TEOS of 6 / 4. This coating solution was applied to the surface of the SiOx film and then dried to form a PVA layer containing Si. The mass per unit area of ​​the PVA layer containing Si was 0.3 g / m 2 The thickness of the Si-containing PVA layer was 0.3 μm.

[0065] In Table 1, the logarithmic decrement of the surface of the second layer on the third layer side was measured by the rigid pendulum method (rigid pendulum type physical property tester RPT-3000W manufactured by A&D Co., Ltd.).

[0066] In Table 1, the indentation hardness of the surface of the fourth layer opposite to the third layer side was measured by a nanoindenter under the following measurement conditions: During the measurement, the sample was fixed horizontally with an epoxy adhesive. (Measurement conditions) Control mode: Displacement control Indentation depth: 30 nm Push-in time: 1s, hold time: 1s, pull-out time: 1s Number of measurement points: 30 points (5 points x 3 points x 2 sets) Measurement interval: 50μm

[0067] (Experimental Example 2) A laminate was obtained in the same manner as in Experimental Example 1, except that the OPP film A was used instead of the PET film and the EVOH coating liquid was used instead of the PVA coating liquid. The mass per unit area of ​​the EVOH layer was 0.61 g / m 2 The surface roughness Sa of the EVOH layer was 0.08 μm.

[0068] (Experimental Example 3) An EVOH layer (thickness 1 μm) was formed by extrusion on the surface of OPP film B via adhesive resin Admer. Thereafter, a laminate was obtained in the same manner as in Experimental Example 1. The mass per unit area of ​​the EVOH layer was 1.21 g / m 2 The surface roughness Sa of the EVOH layer was 0.08 μm.

[0069] (Experimental Example 4) A laminate was obtained in the same manner as in Experimental Example 1, except that the PVA coating liquid was replaced with an ethylene-modified PVA coating liquid.

[0070] (Experimental Example 5) A laminate was obtained in the same manner as in Experimental Example 3, except that an aluminum ingot was used instead of the SiO deposition material, and an oxygen-containing atmosphere was created in the chamber to form an AlOx thin film (thickness 10 nm) instead of a SiOx thin film. The mass per unit area of ​​the EVOH layer was 1.21 g / m 2 The surface roughness Sa of the EVOH layer was 0.08 μm.

[0071] (Experimental Example 6) A laminate was obtained in the same manner as in Experimental Example 4, except that a coating liquid in which the mass ratio of polyvinyl alcohol-based resin to TEOS was 99.5 / 0.5 was used as the coating liquid for forming the second polyvinyl alcohol-based resin layer.

[0072] (Experimental Example 7) A laminate was obtained in the same manner as in Experimental Example 2, except that the second polyvinyl alcohol-based resin layer was not formed.

[0073] (Experimental Example 8) A laminate was obtained in the same manner as in Experimental Example 2, except that the first polyvinyl alcohol-based resin layer was not formed.

[0074] (Experimental Example 9) A laminate was obtained in the same manner as in Experimental Example 2, except that a polyurethane coating liquid was used instead of the EVOH coating liquid.

[0075] (Experimental Example 10) In order to form a PVA layer (second polyvinyl alcohol-based resin layer) containing Si, the following coating solution was prepared. That is, a solution obtained by hydrolyzing TEOS with an acid was mixed with an aqueous PVA solution, and finally, a silane coupling agent dissolved in water / isopropanol was mixed. In this way, a coating solution was prepared in which the mass ratio of PVA, TEOS, and silane coupling agent was 20 / 70 / 10. This coating solution was applied to the surface of the SiOx film, and then dried to form a PVA layer containing Si. Other than this, a laminate was obtained in the same manner as in Experimental Example 3. The mass per unit area of ​​the EVOH layer was 0.61 g / m 2The surface roughness Sa of the EVOH layer was 0.08 μm.

[0076] (Experimental Example 11) A laminate was obtained in the same manner as in Experimental Example 5, except that the coating liquid prepared in Experimental Example 10 was used as the coating liquid for forming the second polyvinyl alcohol-based resin layer. The mass per unit area of ​​the EVOH layer was 0.61 g / m 2 The surface roughness Sa of the EVOH layer was 0.08 μm.

[0077] (Experimental Example 12) A laminate was obtained in the same manner as in Experimental Example 3, except that a PE film was used instead of OPP film B, and the coating liquid prepared in Experimental Example 10 was used as the coating liquid for forming the second polyvinyl alcohol-based resin layer. The mass per unit area of ​​the EVOH layer was 0.61 g / m 2 The surface roughness Sa of the EVOH layer was 0.08 μm.

[0078] (Experimental Example 13) A laminate was obtained in the same manner as in Experimental Example 2, except that a PVA coating liquid was used instead of the EVOH coating liquid, and the coating liquid prepared in Experimental Example 10 was used as the coating liquid for forming the second polyvinyl alcohol-based resin layer. The mass per unit area of ​​the PVA layer was 0.5 g / m 2 The surface roughness Sa of the PVA layer was 0.32 μm.

[0079] (Experimental Example 14) A laminate was obtained in the same manner as in Experimental Example 3, except that the coating liquid prepared in Experimental Example 6 was used as the coating liquid for forming the second polyvinyl alcohol-based resin layer. The mass per unit area of ​​the EVOH layer was 1.21 g / m 2 The surface roughness Sa of the EVOH layer was 0.08 μm.

[0080] [Table 1]

[0081] <Oxygen permeability evaluation> The oxygen permeability of each laminate was measured using a MOCON OX-TRAN in accordance with JIS-K7126-2. The measurement conditions were 30°C and 70 RH%. The oxygen permeability after boiling treatment was measured after immersing each laminate in hot water at 90°C for 30 minutes. The results are shown in Table 2.

[0082] [Table 2]

[0083] As shown in Table 2, the laminates of Experimental Examples 2, 3, 5, and 10 to 14 having the configuration of the present disclosure were confirmed to have excellent gas barrier properties, despite being polyolefin-based laminates. [Explanation of symbols]

[0084] 10...base material layer, 11...first polyvinyl alcohol-based resin layer, 12...Si- or Al-containing thin film layer, 13...second polyvinyl alcohol-based resin layer, 14...sealant layer, 100...gas barrier laminate, 200, 300...packaging material.

[0085] [1] A substrate layer, a first polyvinyl alcohol-based resin layer, a Si- or Al-containing thin film layer, and a second polyvinyl alcohol-based resin layer, in this order; The base layer contains a polyolefin resin, the logarithmic decrement at 100°C is 0.20 or less and the logarithmic decrement at 125°C is 0.30 or less, as measured by a rigid pendulum type physical property tester, on the surface of the first polyvinyl alcohol-based resin layer on the side in contact with the Si- or Al-containing thin film layer; the surface of the second polyvinyl alcohol-based resin layer has an indentation hardness of 0.5 to 1.0 GPa when measured with a nanoindenter; Gas barrier laminate. [2] The gas barrier laminate according to [1], wherein the second polyvinyl alcohol-based resin layer contains Si. [3] The gas barrier laminate according to [1] or [2], wherein the second polyvinyl alcohol-based resin layer is a cured product of a raw material containing a polyvinyl alcohol-based resin and a silane compound, and the amount of the silane compound in the raw material is 0.3 to 5.0 parts by mass per 1 part by mass of the polyvinyl alcohol-based resin. [4] The gas barrier laminate according to any one of [1] to [3], wherein the Si- or Al-containing thin film layer contains at least one of silicon oxide and aluminum oxide. [5] The gas barrier laminate according to any one of [1] to [4], wherein the Si- or Al-containing thin film layer has a thickness of 5 to 80 nm. [6] The mass per unit area of ​​the first polyvinyl alcohol-based resin layer is 0.1 to 10 g / m 2 The gas barrier laminate according to any one of [1] to [5], [7] The gas barrier laminate according to any one of [1] to [6], wherein the surface roughness Sa of the first polyvinyl alcohol-based resin layer on the side in contact with the Si- or Al-containing thin film layer is 0.2 μm or less. [8] The gas barrier laminate according to any one of [1] to [7], wherein the base layer is a propylene monopolymer layer. [9] A gas barrier laminate according to any one of [1] to [8], a sealant layer provided on a surface of the gas barrier laminate; A packaging material comprising:

[10] The base layer of the gas barrier laminate is made of a polyolefin resin, The sealant layer is made of a polyolefin resin, The packaging material according to [9], wherein the polyolefin resin content is 90 mass% or more based on the total mass of the packaging material.

[11] A tubular body having one end closed; A spout portion attached to the other end of the body portion, A tube container, the body of which is composed of a film containing the gas barrier laminate according to any one of [1] to [8] and a layer of unstretched polyolefin.

Claims

1. A substrate layer, a first polyvinyl alcohol-based resin layer, a Si- or Al-containing thin film layer, and a second polyvinyl alcohol-based resin layer are provided in this order; The base layer contains a polyolefin resin, the first polyvinyl alcohol-based resin layer contains a polyvinyl alcohol-based resin that is EVOH; the second polyvinyl alcohol-based resin layer is a cured product of a raw material containing a polyvinyl alcohol-based resin that is PVA and a silane compound that is TEOS, and the amount of the silane compound in the raw material is 0.3 to 5.0 parts by mass per 1 part by mass of the polyvinyl alcohol-based resin; the logarithmic decrement at 100° C. is 0.14 or more and 0.20 or less, and the logarithmic decrement at 125° C. is 0.24 or more and 0.30 or less, as measured by a rigid pendulum type physical property tester, on a surface of the first polyvinyl alcohol-based resin layer on the side in contact with the Si- or Al-containing thin film layer; the surface of the second polyvinyl alcohol-based resin layer has an indentation hardness of 0.5 to 1.0 GPa as measured by a nanoindenter; Gas barrier laminate.

2. The gas barrier laminate according to claim 1 , wherein the Si- or Al-containing thin film layer contains at least one of silicon oxide and aluminum oxide.

3. 3. The gas barrier laminate according to claim 1, wherein the Si- or Al-containing thin film layer has a thickness of 5 to 80 nm.

4. The mass per unit area of ​​the first polyvinyl alcohol-based resin layer is 0.1 to 10 g / m 2 The gas barrier laminate according to any one of claims 1 to 3,

5. 5. The gas barrier laminate according to claim 1, wherein the first polyvinyl alcohol-based resin layer has a surface roughness Sa of 0.2 μm or less on a side in contact with the Si- or Al-containing thin film layer.

6. The gas barrier laminate according to any one of claims 1 to 5, wherein the base layer is a propylene monopolymer layer.

7. The gas barrier laminate according to any one of claims 1 to 6, wherein the base layer is an OPP film.

8. The gas barrier laminate according to any one of claims 1 to 7, wherein the base layer has a thickness of 18 to 25 µm.

9. 9. The gas barrier laminate according to claim 1, wherein the first polyvinyl alcohol-based resin layer has a thickness of 0.5 to 1 μm.

10. The gas barrier laminate according to any one of claims 1 to 9, a sealant layer provided on a surface of the gas barrier laminate; A packaging material comprising:

11. the base layer of the gas barrier laminate is made of a polyolefin resin, The sealant layer is made of a polyolefin resin, The packaging material according to claim 10, wherein the content of the polyolefin resin is 90 mass% or more based on the total mass of the packaging material.

12. A tubular body portion having one end closed; A spout portion attached to the other end of the body portion, 10. A tube container, the body of which is constituted by a film comprising the gas barrier laminate according to any one of claims 1 to 9 and a layer of unstretched polyolefin.

Citation Information

Patent Citations

  • Polyolefin film with barrier property

    JP1996245816A

  • Gas barrier olefin resin laminate

    JP1997201897A

  • Gas-barrier polypropylene thin film

    JP1998235777A

  • Laminated film having gas barrier property

    JP1999020102A

  • o ▲ Bottom 2 ▼ Packaging material with barrier

    JP2000508260A